1980
DOI: 10.1002/jbm.820140305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxyapatite impregnation on skeletal bonding of porous coated implants

Abstract: Skeletal fixation of permanent implants by new methods such as fixation by mechanical interlocking of bone with porous prosthetic coatings or chemical bonding with bioactive materials shows growing potential. This paper reports on the resulting skeletal fixation of a combined porous and bioactive material. Metal plugs with a porous metal fiber coating impregnated with hydroxyapatite were implanted for 2, 4, and 12 weeks and were compared to the parent porous, nonbioactive, metal fiber material. Statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(97 citation statements)
references
References 9 publications
1
86
0
2
Order By: Relevance
“…Ducheyne et al (1980) found a far greater amount of bony ingrowth after 2 and 4 weeks with the HA-impregnated samples.…”
Section: Discussionmentioning
confidence: 75%
“…Ducheyne et al (1980) found a far greater amount of bony ingrowth after 2 and 4 weeks with the HA-impregnated samples.…”
Section: Discussionmentioning
confidence: 75%
“…Some have reported that there is no clinical advantage 14 while others have demonstrated a significant increase in bone ingrowth. 15,16 We have investigated bone ingrowth and attachment to an HA-coated porous titanium surface, a plain porous titanium surface and a roughened titanium (Interlok) surface finish in one femoral design from specimens obtained at post-mortem.…”
mentioning
confidence: 99%
“…Many researchers later on discovered some other ceramics, glass-ceramics and composites also have the same property (De Groot, 1983De Groot et al, 1990;De Groot & LeGeros, 1988;Ducheyne et al, 1980;Gross et al, 1988;Gross and Strunz, 1985;Hench, 1987Hench, , 1988Hench & Ethridge, 1982;Hench et al, 1971;Hench & Wilson, 1984;Holand et al, 1985;Hulbert et al, 1987;Jarcho, 1981;Kitsugi et al, 1989;Kokubo et al, 1986;Kokubo et al, 1982;Nakamura et al, 1985;Wilson et al, 1981;Yamamuro et al, 1990b;Yamamuro et al, 1988;Yoshii et al, 1988). He defined these glasses as 'bioactive glass' and since then it has been used mostly as a reconstructive material for damaged hard tissues such as bone (Hench, 2006;Hench et al, 1971).…”
Section: Bioactive Glass Materialsmentioning
confidence: 99%